2019
DOI: 10.1039/c9bm00688e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of siRNA transfection by the optimization of fatty acid length and histidine content in the CPP

Abstract: Extracellular synthetic nucleic acids, such as siRNAs, are unable to reach their intended targets efficiently.Therefore, delivery methods such as cell-penetrating peptides (CPP), which increase their transport, could enhance the potency of siRNA as therapeutic agents. The CPP NickFect55 (NF55) is an efficient peptide-based delivery vector, which has been previously used to deliver plasmid DNA into cells in vivo.To achieve higher intracellular delivery and bioactivity from the delivered cargo, we designed a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…Porosk et al, prepared a series of histidine-containing lipopolymers to optimize siRNA delivery [ 81 ]. Previously, the group modified KALA containing lipopolymers with a pH-buffering chloroquine analog to enhance siRNA delivery [ 82 ].…”
Section: Lipopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Porosk et al, prepared a series of histidine-containing lipopolymers to optimize siRNA delivery [ 81 ]. Previously, the group modified KALA containing lipopolymers with a pH-buffering chloroquine analog to enhance siRNA delivery [ 82 ].…”
Section: Lipopeptidesmentioning
confidence: 99%
“…They determined that some histidine patterns that were N-terminal to the KALA group were effective carriers in vitro and in vivo. After a single intravenous injection, one histidine-containing analog, H6-20 (also named NickFect70), silenced factor VII in the liver of mice by about 60% compared to untreated controls [ 81 ]. Chen et al demonstrated that a stearylated histidine-containing cationic peptide in complex with siGADPH was as effective as silencing its target in vitro as lipofectamine [ 83 ].…”
Section: Lipopeptidesmentioning
confidence: 99%
“…Therefore, many efforts have been undertaken to promote the endosomal escape of CPPs 46–48 . Incorporation of histidine residues is a simple and effective approach for this purpose 49–52 . To evaluate the endosomal escape of HNLS‐3 containing histidine residues, we used confocal microscopy to observe the colocalization between FITC‐labeled HNLS‐3 and LysoTracker Red‐labeled endosomes/lysosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the preformed protein corona was harnessed to convert nanoparticles targetable to tumour cells. For that, particles were coated with tumour-specific antibodies and human serum albumin that helps to prevent phagocytosis of the particles [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%